Efektivitas Art Therapy Untuk Pasien dengan General Anxiety Disorder(GAD) - Nagara, Angga Dipa; Rifa’i, M. Ridwan (Jurnal Medika Cendikia, 2020)
The presence of Anxiety Disorder is associated with a lower quality of life (quality of life) and a negative impact on psychosocial functioning. The combination of psycho therapy with CBT is recommended but about 50% of individuals with IK are not benefiting from CBT or would rather not take medication or prefer non-verbal therapy individuals may benefit from Art Therapy. The aim of this paper is to see how effective Art Therapy is for patients with Anxiety Disorders. The process of searching for articles using the PubMed, ScienceDirect, and DOAJ databases with the keywords "anxiety" or "psychosocial", and "generalized anxiety disorder", and "art", and "art therapy", as well as the year the article was published, namely 2010- 2020. Based on the search results, 223 articles were obtained. Then the articles were selected according to the full text inclusion criteria, the suitability of the title with keywords, the RCT design, in English. The exclusion criteria were articles published in 2010 and above in 2020, only available in abstract, cross-sectional design, and Arabic. So, 6 articles were obtained for analysis. Art therapy or Arth therapy can reduce general anxiety. Accessing the database and paid articles